Le nationalisme de Roger Duhamel, 1927-1947 - Langevin, Martin (Les Cahiers d'histoire du Québec au XXe siècle, 1994)
Keywords: Montréal-Matin; Nationalisme

La pensée politique de L'Action française de Montréal, 1917-1928 - Dupuis, Jean-Claude (Les Cahiers d'histoire du Québec au XXe siècle, 1994)
Keywords: Action française (L'); Idéologies

Afro-Canadian Activism in the 1960s - Stamadianos, Peter (Université Concordia, 1994)
Afro-Canadian activism became increasingly militant in the 1960s. The rise in militancy in the Afro-American leadership of the 1960s was one factor contributing to the new era of black politics in Canada. Increased immigration from the West Indies also encouraged the proliferation of Afro-Canadian organizations dedicated to challenging racial discrimination. Afro-Canadian activism, however, developed in a substantially different manner than black politics in the United States. On the whole, most Afro-Canadian organizations and leaders were considerably less militant in their tactics and strategies than their counterparts in the United States. Internecine divisions over ancestral origin were also more pronounced in Canada where the black population was ethnically heterogeneous when compared to the Afro-American community.
Keywords: Africains; Noirs

Exchange of Opinion in the Canadian Press on the Eve of the Union, 1839-1840 - Williams, Garth (Université de Montréal, 1994)

La formation des intellectuels québécois dans l'entre-deux-guerres - Pomeyrols, Catherine (Université Michel de Montaigne-Bordeaux 3, 1994)
Keywords: Laurendeau, André; Minville, Esdras

Retailing Fashion in Montreal: A Study of Stores , Merchants and Assortments, 1845-1915 - Sifton, Elizabeth (Université Concordia, 1994)
Keywords: Commerce de détail; Marchands; Vêtements